2016
DOI: 10.1016/j.stem.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Lineage Diversification, Simplified

Abstract: Hematopoiesis is a complex process that requires a high degree of transcriptional diversification during lineage commitment and differentiation. de Graaf et al. (2016) have now generated a comprehensive gene expression dataset that allows cell-type-specific genes as well as associated transcription factor expression patterns to be readily identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In multiple online databases, we found that IL5RA, LY9, SLAMF7, and ICAM1, biomarkers of the haematopoietic cell lineage pathway, were significantly correlated with metastasis and prognosis in patients with STS. The haematopoietic cell lineage pathway is a complex renewal and differentiation process of blood cells, in which haematopoietic stem cells (HSCs) differentiate into common lymphoid progenitors (CLPs) and common myeloid progenitors (CMPs), ultimately promoting the lymphoid lineage and the myeloid lineage, respectively [51,52]. Defects in the haematopoietic cell lineage pathway reportedly contribute to malignant cell transformation [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple online databases, we found that IL5RA, LY9, SLAMF7, and ICAM1, biomarkers of the haematopoietic cell lineage pathway, were significantly correlated with metastasis and prognosis in patients with STS. The haematopoietic cell lineage pathway is a complex renewal and differentiation process of blood cells, in which haematopoietic stem cells (HSCs) differentiate into common lymphoid progenitors (CLPs) and common myeloid progenitors (CMPs), ultimately promoting the lymphoid lineage and the myeloid lineage, respectively [51,52]. Defects in the haematopoietic cell lineage pathway reportedly contribute to malignant cell transformation [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Cell differentiation has been studied in great molecular detail, and some conceptual underpinnings have started to emerge, for example, during differentiation the ability to express different gene expression programs is gradually restricted and the potency reduced. 4,5 In recent times, single-cell RNA-seq and other profiling studies are revealing a more complex picture. It appears that many multipotent and pluripotent cell populations are heterogeneous in terms of surface markers and gene expression profiles.…”
mentioning
confidence: 99%